ANALISIS FISIBILITAS PENGENAAN CUKAI ATAS MINUMAN BERPEMANIS (SUGAR-SWEETENED BEVERAGES) - Ardiansyah, Benny Gunawan (Badan kebijakan Fiskal, 2017)
The increasing of overweight and obesity prevalence took place around the world, including Indonesia. The World Health Organization (WHO) suggested that all countries had to apply fiscal policies and influence the consumption patterns. One of the manufacturing product, that should be controlled for its consumption, is a sugar-sweetened beverage (SSB). This study tried to analyze the imposing of excise on SSB using the qualitative methods. The results indicated that the imposition of excise on SSB was urgent. Any objection and resistance, for economic or technical and administration reason, seems to be easily contolled so it could be applied soon. The levy excise on SBB will avoid some public health problems in the future and Indonesia won’t loose any momentum in utilizing demographic bonuses.